Efektifitas Terapi Garam sebagai Upaya Pengobatan Granuloma Umbilikal - Prihatanti, Nur Rohmah; Aprilea, Noor Adha (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2022)
Umbilical granuloma is granular tissue that appears in the center of the umbilical cord after the baby's umbilical cord is detached. Umbilical granuloma is reported to occur in 1 in 500 newborns. Umbilical granuloma is closely associated with delayed formation of the umbilical cord and the presence of an inflammatory process or mild infection in the umbilical cord. A literature study was conducted to determine the effectiveness of salt therapy in the treatment of umbilical granuloma. The criteria for the articles reviewed are articles with a range of 2018-2022 and using the Google Scholar database. The keywords used are